2017
DOI: 10.1111/1346-8138.13808
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of the benign melanocytic universe: Dermoscopic–histopathological correlation in nevi

Abstract: The broad universe of "melanocytic nevi" includes a variety of different subtypes, which can be classified either due to their morphology, epidemiology, genetic alterations or risk for developing melanoma. Regarding morphology, on the one hand macroscopic/clinical and on the other hand histopathological appearance were used to subdivide in the past, often resulting in confusion and poor interobserver agreement, while nowadays dermoscopy presents the clinician's precious bridge between naked-eye examination and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 50 publications
0
10
0
2
Order By: Relevance
“…These initial melanomas may be incompletely developed melanomas [ 34 ]. Woltsche et al ., in a review, reanalysed melanocytic lesions and reaffirmed that there are lesions that cannot be classified using the clinical, dermatoscopic and histopathological criteria; such lesions would be termed atypical melanocytic proliferations of uncertain significance [ 35 ]. In this study, atypical melanocytic nevi were identified in 45.1% of the lesions.…”
Section: Discussionmentioning
confidence: 99%
“…These initial melanomas may be incompletely developed melanomas [ 34 ]. Woltsche et al ., in a review, reanalysed melanocytic lesions and reaffirmed that there are lesions that cannot be classified using the clinical, dermatoscopic and histopathological criteria; such lesions would be termed atypical melanocytic proliferations of uncertain significance [ 35 ]. In this study, atypical melanocytic nevi were identified in 45.1% of the lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In late adulthood, naevi become dermal or tend 62Á9 (53Á7-68Á4) Calendar year at first visit to disappear in elderly people, especially on areas other than the head and neck. 19 Genes involved in this senescence process are not well established, but BRAF, CDKN2A and telomere genes are likely to play a role 20 in addition to immune-related genes. 21,22 Previous studies on naevus counts have shown that genetic factors are important for naevus patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomically, the structure of facial skin has poor rete ridges, and instead, it has a large number of hair follicles. When pigmented cells exist in the epidermis, homogeneous pigmentation is disrupted by unpigmented follicular openings forming pseudonetwork 5 .…”
Section: Discussionmentioning
confidence: 99%